Xenophobia attacks and Africa’s regional integration: a case of South Africa’s xenophobia attacks from 2000 - 2015 - Saya, Kudzai (Midlands State University, 2017)
The issue of xenophobia attacks in South Africa has become a problematic phenomenon in the African continent with the cases ofZambia and South Africa. This xenophobic tendence is based on prejudice and hatred directed towards foreign nationals specifically black Africans who are deemed by the native groups as persistent threats to their entitlements like employment security, accommodation, resource distribution and other various opportunities within the political, economic, socio-cultural and technological premises just to mention these few. As such, the purpose ofthis research work was to establish the background ofthe phenomenon ofxenophobia and its related violence in the South African context, what ripple effects its brings about in various levels of the society and how it inturn affects the idea of Africa's regional integration in bi-lateral and multi-lateral state interaction platforms. It was also dwelt upon that regional integration is a feasible alternative to bring about the much needed development in a collective effort and outcome basis. Various schools of thought support this notion as they generally agree that African states are generally weak and vulnerable therefore they should achieve unity of purpose to ensure for collective development as well as establishing sovereignty and security from external intervention exercises by super powers in the international arena. Various conclusions have been reached from information gathered during the research as to the opinions, views and comments from respondents that were consulted and further recommendations were provided as to what more that can be done to mitigate the problem of xenophobic attacks which would consequently ensure for the successful realisation of the various efforts towards regional integration on the African continent.